Estimulação transcraniana por corrente contínua na fase crônica da Chikungunya: protocolo para um ensaio clínico randomizado - Nascimento, Abraão Sérvulo do (2022)
Introduction: Chikungunya virus infection is still an epidemic in Brazil with an incidence of 59.4 cases per 100,000 in the Northeast region. More than 60% of patients have chronic recurrent arthralgia, and there are no specific therapeutic agents to treat and rehabilitate people in the chronic phase of chikungunya. Persistent pain can lead to disability, requiring long-term pharmacological treatment. Non-drug therapies such as transcranial direct current stimulation (tDCS) emerge as a promising complementary approach for these patients. Objectives: to evaluate the effects of tDCS on pain and functionality of individuals in the chronic phase (symptoms persisting for more than 3 months) of chikungunya using anodic tDCS in the primary motor cortex (C3/Fp2 assembly). Methods: this is a protocol of a clinical trial, parallel, double-blind, randomized and controlled. Forty participants of both sexes with chronic chikungunya (minimum 3 months of initial infection) will be randomized to an active or sham group. A total of ten consecutive sessions lasting 20 min each will be administered over two weeks, using a single-phase direct current with an intensity of 2 mA for 20 min. Participants in both groups will be assessed at baseline, immediately after the 10th session, 2 weeks (first follow-up) and 4 weeks (second follow-up) after the intervention. As a primary outcome, we will have pain assessed using a numerical rating scale (NRS) and algometry to record pressure pain threshold (PPTh) and pressure pain tolerance (PPTo). Secondary outcomes will be functionality (HAQ), muscle strength (Handgrip dynamometer) and quality of life (SF-36). The effects of stimulation will be calculated using a mixed analysis of variance (ANOVA) model. Expected results: The application of tDCS in the described assembly is already recommended for chronic pain syndromes and rheumatic diseases. It is expected that the outcomes will improve only in the active group, contributing to the strengthening of this resource for this population. This way we will have one more non-pharmacological therapeutic option available and accessible, and additional data for the scientific discussion around clinical policies and future trials.